Caso para diagnóstico Case for diagnosis - Flávia Vieira Brandão; Cláudia Márcia Resende Silva; Bernardo Gontijo; Antônio Carlos Martins Guedes (Sociedade Brasileira de Dermatologia, 2009)
Fibromatose hialina juvenil e hialinose sistêmica infantil são desordens autossômicas recessivas, raras da infância. À histologia, há depósito de material hialino na derme e subcutâneo. As características clínicas principais são: lesões pápulo-nodulares, hipertrofia gengival, contratura articular, lesões ósseas osteolíticas e retardo no crescimento. Mutações no mesmo gene foram identificadas nas duas condições, sugerindo que sejam espectros da mesma doença. Juvenile hyaline fibromatosis and infantile systemic hyalinosis are rare autossomal recessive disorders with onset in infancy or early childhood. Histological examination shows deposit of hyaline material in the dermis and subcutaneous tissue. Clinical features include papulonodular skin lesions, gingival hypertrophy, flexion contractures of joints, osteolytic bone lesions and stunted growth. Mutations in the same gene were detected in both conditions, suggesting that they may be variants of the same disorder.